Patient and clinician perspectives on a patient‐facing dashboard that visualizes patient reported outcomes in rheumatoid arthritis - Lucy H. Liu; Sarah B. Garrett; Jing Li; Dana Ragouzeos; Beth Berrean; Daniel Dohan; Patricia P. Katz; Jennifer L. Barton; Jinoos Yazdany; Gabriela Schmajuk (Wiley, 2020)
Abstract Background Poor patient‐clinician communication around patient‐reported outcomes (PROs) is a barrier to the effective management of rheumatoid arthritis (RA). We aimed to develop an RA 'dashboard' that could facilitate conversations about PROs and that would be acceptable to a wide range of patients, including English and Spanish speakers and patients with adequate or limited health literacy. Methods A diverse group of RA patients along with clinicians from two academic rheumatology clinics joined separate focus groups. We solicited feedback and made iterative changes to mock‐ups of an RA dashboard that visualized PROs using a human‐centred design process. We used the thematic analysis method to identify and characterize themes from the focus groups and used these insights to refine the dashboard. Results We conducted six focus groups involving 25 RA patients and three groups with 11 clinicians. Patients and clinicians agreed that the dashboard could enhance communication about PROs and RA disease activity and could promote patient self‐management. Patients varied in their (a) comprehension, (b) preferences for the display and features of the dashboard, and (c) desired uses for the dashboard. Clinicians expressed significant concerns about the logistics of using the dashboard in clinical practice. Conclusion Using principles of human‐centred design, we created an RA dashboard that was well‐accepted among patients and clinicians. The ability to customize the data display is important for tailoring the dashboard to patients with diverse needs and preferences. Special attention should be given to feasibility concerns voiced by clinicians.